Perancangan Buku Ilustrasi Cerita Rakyat Pulau Kemaro dari Palembang - Randy Enggo; Ratih Mahardika (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Folklore is an important part of forming a creative and critical mindset in elementary schools in theface of the COVID-19 pandemic. With folklore to children, it will help children know and get interestingreading material while filling time during the COVID-19 pandemic. The Kemaro Island Folklore,originating from South Sumatra, is one of the various folklores that exist in Indonesian society. KemaroIsland is an island in the middle of the Musi River and about 7 km from the city of Palembang. The legendof Kemaro Island is heard among the people of the city of Palembang, who generally tell about the lovestory between Princess Siti Fatimah from the Sriwijaya Kingdom and a prince from a country named TanBun An. The results of the design are characters in the form of children's storybook media inspired by thelegendary folklore of Kemaro Island from Palembang as historical local wisdom for school children. Thisdesign uses a design method by Eric Karjaluoto which includes (analysis of supporting data), planning(illustrating character design), creative (combining the results of illustrations with story narratives) andapplication (character implementation). can produce interesting readings and introduce elementary schoolchildren to Kemaro Island folklore.